2013
DOI: 10.1016/j.pan.2013.07.027
|View full text |Cite
|
Sign up to set email alerts
|

How and when should NSAIDs be used for preventing post-ERCP pancreatitis? A systematic review and meta-analysis

Abstract: Background: Non-steroidal anti-inflammatory drugs (NSAIDs) have been shown to be efficacious to prevent pancreatitis after endoscopic retrograde cholangiopancreatography (ERCP). However, the target patients, the type of NSAID, the route of administration and the time of drug delivery remain unclear, as well as the potential efficacy in reducing the severity of pancreatitis, length of hospital stay and mortality. The objective of the study was to evaluate these questions by performing a systematic review and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 29 publications
0
11
0
3
Order By: Relevance
“…The recent analysis by Sethi et al, 14 including seven trials, 9,22,23,27,[36][37][38] involved studies assessing rectal indomethacin and diclofenac. Compared with other analyses, which concluded the efficacy of NSAIDs in general, 13,15,30,31 the analysis by Sethi et al 14 concluded that rectal NSAIDs were effective. However, the analysis included studies involving high-risk patients only.…”
Section: T Was Shown In Our Meta-analysis That Rectal Nsaidsmentioning
confidence: 88%
See 4 more Smart Citations
“…The recent analysis by Sethi et al, 14 including seven trials, 9,22,23,27,[36][37][38] involved studies assessing rectal indomethacin and diclofenac. Compared with other analyses, which concluded the efficacy of NSAIDs in general, 13,15,30,31 the analysis by Sethi et al 14 concluded that rectal NSAIDs were effective. However, the analysis included studies involving high-risk patients only.…”
Section: T Was Shown In Our Meta-analysis That Rectal Nsaidsmentioning
confidence: 88%
“…Our findings resemble several previous meta-analyses on this topic. Among the previous meta-analyses, the analyses by Rustagi and Njei, 30 by Puig et al, 13 by Sajid et al, 31 and by Ding et al, 15 all reported that NSAIDs seemed to have an advantage of reducing the incidence of PEP. However, all of the analyses 13,15,30,31 involved studies that were heterogeneous concerning the route of administration.…”
Section: T Was Shown In Our Meta-analysis That Rectal Nsaidsmentioning
confidence: 99%
See 3 more Smart Citations